Observing the polarization of cosmic-ray muons in student physics laboratory. (1st March 2021) - Xu, Jisi; Chu, Anjun; Yuan, Zi; Song, Xinliang; Cheng, Tianle; Yi, Han; Wang, Yijie; Chang, Ying; Zhang, Zhao; Xiao, Zhigang
Abstract: An undergraduate-level student experiment has been designed and implemented to measure the forward–backward asymmetry of the decay of the cosmic-ray muons, offering a pedagogical view to the parity violation in weak interactions. The detector system consists of six plastic scintillators installed vertically in row. The backward–forward asymmetry of the decay e −   and  e + with respect to the muon motion direction is correlated with the incident depth of the muon stopped in the scintillator. MC simulations have been carried out in order to better interpret the data and optimize the data analysis. The forward–backward asymmetry of 0.051 ± 0.027 is deduced for the decay of cosmic-ray muons in the energy range being studied. The results are consistent with the picture of parity violation in weak interactions. The experiment can be constructed by the senior undergraduate students under the guidance of the course teacher.